A keyword analysis of stance and engagement in three-minute thesis (3MT) presentations - Yang, Wenhsien (Penerbit Universiti Kebangsaan Malaysia, 2020)
Due to the increasing influence of promotional culture on academic discourse, new marginal genre texts with informative and promotional purposes are emerging. In this study, we investigated a novel promotional but under-researched academic spoken genre, 3MT (threeminute thesis) presentations, which only allow the speakers 3 minutes to promote their research findings. We generated keywords of this genre using size effect metrics to identify the features of 3MT presentations delivered by PhD candidates and trained undergraduate ESP learners. The addressors were compared in their use of personal pronouns to present their stance and to interact with the audience. The results revealed that the PhD candidates tended to highlight the values and rationale of their research, whereas the ESP learners placed greater emphasis on their methodology. The PhD candidates were better at using rhetorical devices, i.e. reader pronouns and inclusive we, to invite the audience into their discourse community. Some similarities between the two groups were also identified. For example, ‘you’ was less deployed by both groups compared with its use in other academic spoken genre texts. Our study shows that genres are not only evolving and changing but are also heavily affected by technology advancements. Findings can also help ESP practitioners better prepare learners to make persuasive presentations in minimal time by employing personal pronouns.